2019
DOI: 10.16986/huje.2019050786
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye deki Öğrencilerin Fen Okuryazarlığını Etkileyen Faktörler Nelerdir PISA 2015 Verisine Dayalı Bir Hiyerarşik Doğrusal Modelleme Çalışması

Abstract: Bu çalışmanın temel amacı, 2015 yılındaki PISA uygulamasında elde edilen veriden yararlanılarak, Türkiye'deki öğrencilerin fen okuryazarlığını etkileyen öğrenci ve okul düzeyindeki değişkenlerin belirlenmesidir. Böylece öğrencilerin fen okuryazarlığı düzeylerini yordayan değişkenlerden oluşan hiyerarşik bir modelin elde edilmesi hedeflenmiştir. Özellikle 2015 yılındaki PISA uygulamasında Türkiye'nin ortalama başarı düzeyindeki keskin düşüş göz önüne alındığında bu çalışmanın sonuçları daha da büyük önem kazanm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…As expected, the presence of a negative relationship between one of the Level-1 predictors, i.e., the shortage of educational materials, and students' achievement is also supported by other studies in the literature (Berberoğlu et al, 2019;Üstün, Özdemir, Cansız, & Cansız, 2020). Considering this relationship, it is necessary to increase the improvements in educational materials and the compensatory measures for the deficiencies.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 77%
“…As expected, the presence of a negative relationship between one of the Level-1 predictors, i.e., the shortage of educational materials, and students' achievement is also supported by other studies in the literature (Berberoğlu et al, 2019;Üstün, Özdemir, Cansız, & Cansız, 2020). Considering this relationship, it is necessary to increase the improvements in educational materials and the compensatory measures for the deficiencies.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 77%
“…This finding constituted a reflection of the literature. The studies focusing on PISA results showed that school-level variables were more dominant than student-level variables in terms of variance in outcome variable (Alacacı & Erbaş, 2010;Astrom & Karlsson, 2007;Özberk, Atalay-Kabasakal, & Boztunç-Öztürk, 2017;Üstün, Özdemir, Cansız, & Cansız, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, student behaviours hindering learning decreased reading literacy; teacher behaviours hindering learning increased reading literacy. Findings related to negative relationship between student behaviours hindering learning were parallel to the literature (Özer- Özkan, 2016;Üstün, Özdemir, Cansız, & Cansız, 2019). On the other hand, findings related to positive relationship between teacher behaviour hindering learning served blur in the literature since the literature has studies showing positive relation, negative relation, and no relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu bağlamda bilimin ışığında yeni nesilleri fen okuryazarı bireyler olarak yetiştirmek önem arz etmektedir (Kılınç, 2018). Fen okuryazarı bireylerin bilim üretilirken geçilen aşamaları bilmesi (Jurecki & Wander, 2012) okulda karşılaşılan anahtar fen kavramlarını ve teorik bilgiyi günlük yaşama aktarabilmesi beklenmektedir (Suryanti, İbrahim & Lede, 2018;Üstün, Özdemir, Cansız & Cansız, 2019). Guthrie'ye (1952) göre bilgi, işin bilişsel boyutunu, beceri ise belirli bir sonuca ulaşma boyutunu kapsamaktadır (Akt: Turan 2014).…”
unclassified